2011
DOI: 10.1021/la201767p
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Lipid–Based Lyotropic Liquid Crystals in Presence of Colloidal Nanoparticles

Abstract: We have investigated the microstructure and phase behavior of monoglyceride-based lyotropic liquid crystals in the presence of hydrophilic silica colloidal particles of size comparable to or slightly exceeding the repeat units of the different liquid crystalline phases. Using small angle X-ray scattering (SAXS) and differential scanning calorimetry (DSC), we compare the structural properties of the neat mesophases with those of the systems containing silica colloidal particles. It is found that the colloidal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 52 publications
6
19
0
Order By: Relevance
“…The SAXS profile of dry SPIONs (Figure 2c, red curve) is characterized by an intense peak (centered at 0.07 Å -1 ), which is slightly shifted at higher scattering vectors with respect to the extra-peak in the corresponding mixed mesophase. We attribute the peaks observed for the dry films as arising from interparticle correlations, thereby ascribing the extra-peaks in the hybrid samples to a partial clusterization of NPs along the grain boundaries of the polycrystalline mesophases, as previously shown for similar systems in other studies [13,43,44]. The difference in the correlation length of SPIONs and AuNPs in the dry film might be both related to the core differences or to the slightly different hydrophobic coating of NPs, which might lead to a different arrangement of the alkyl chains between the neighboring NPs.…”
Section: Small-angle X-ray Scattering (Saxs)supporting
confidence: 73%
See 1 more Smart Citation
“…The SAXS profile of dry SPIONs (Figure 2c, red curve) is characterized by an intense peak (centered at 0.07 Å -1 ), which is slightly shifted at higher scattering vectors with respect to the extra-peak in the corresponding mixed mesophase. We attribute the peaks observed for the dry films as arising from interparticle correlations, thereby ascribing the extra-peaks in the hybrid samples to a partial clusterization of NPs along the grain boundaries of the polycrystalline mesophases, as previously shown for similar systems in other studies [13,43,44]. The difference in the correlation length of SPIONs and AuNPs in the dry film might be both related to the core differences or to the slightly different hydrophobic coating of NPs, which might lead to a different arrangement of the alkyl chains between the neighboring NPs.…”
Section: Small-angle X-ray Scattering (Saxs)supporting
confidence: 73%
“…The most explored amphiphilic scaffolds are lipid vesicles, but more recently some studies have addressed the insertion of inorganic NPs [12,13] into non-lamellar lipid assemblies formed through self-assembly of polymorphic lipids. While some applicative examples have been reported, a fundamental understanding of the impact of NPs on lipid phase behavior, necessary to design these materials for a specific biomedical application is, to date, very limited.…”
Section: Introductionmentioning
confidence: 99%
“…35 36 and have recently demonstrated this experimentally from a curved lipid bilayer. 37 They found that the transition from SUVs to the cubic phase has an intermediate tetrahedral packed bilayer vesicle stage before forming the larger cubosomes.…”
Section: Resultsmentioning
confidence: 81%
“…Venugopal et al 47 studied the phase behaviour of monolinolein, which has a single chain rather than the two of DOPE, with added hydrophilic silica NPs of 5 nm diameter. They found that an increasing concentration of NPs decreased the lattice parameter of the cubic phase and that at higher concentrations the NPs exhibited an independent structure factor peak in the SAXS patterns, which indicated that the NPs were macrophase separated rather than incorporated into the structure and that they dehydrated the lipid mesophase by removal of water from lipid head groups to stabilise the NP aggregates.…”
Section: Resultsmentioning
confidence: 99%